Micro energy harvesting via piezoelectric and electromagnetic dynamics for higher power output - Mohd Tahir, Mohamad Safiddin; Wahid, Azni Nabela; Mohamad Hanif, Noor Hazrin Hany; Janin, Zuriati (IEEE, 2023)
Micro enery harvesting is a promising technology for powering small-scale electronic devices using ambient sources which are normally vibrating at low frequencies. Limitations arise when relying solely on a single energy conversion mechanism, such as the exclusive use of piezoelectric beams. Piezoelectric beams excel at high-frequency energy conversion, leaving low-frequency vibrations untapped. To address this issue, a hybrid energy harvester integrating both piezoelectric beams and magnetic coils emerges as a solution to complement the capability of a piezoelectric harvester. In this work, a copper wound coil is added to an energy harvester assembly that consist of a piezoelectric beam, an eccentric mass and NdFeB permanent magnets that act as proof mass. Each time the eccentric mass passes the beam, the magnets at a fixed distance, repel each other. This simultaneously change magnetic flux around the wound copper coil to generate a larger amount of current. This proposed hybrid configuration produced the highest energy output as compared to the piezoelectric only or electromagnetic only energy harvester, when subjected to a 5 Hz vibration input. This research demonstrated the ability of the hybrid energy harvester to produce electrical power at a low frequency input, which provides optimistic possibility to cater for the energy demand for wearable electronic and wireless devices.